Leveraging traditional liquid formulations usage in organic agriculture in India - A comprehensive review - Ajmal , S S; Ramesh, T; Rathika, S; Sakthivel , K; Kokilavani, S; Kalaimathi , V (Plant Science Today, 2025)
In India, the transition from traditional agriculture to inorganic farming in the post-Green Revolution era has led to environmental degradation and adverse climatic changes. Eco-friendly farming method, such as organic farming, offers viable solutions to address these challenges. Organic farming has gained popularity around the world due to consumer recognition for its health benefits and environmental sustainability. The area under organic farming in India has expanded significantly over the years. Indigenous Technical Knowledge (ITK) plays a crucial role in the success of organic farming. ITK integrates traditional wisdom with scientific knowledge, offering locally adaptable, cost-effective, and sustainable solutions for organic agriculture. This paper provides an overview of traditionally prepared liquid formulations and their role in organic farming, focusing on their preparation methods, applications, and benefits. Various research studies have demonstrated the effectiveness of these traditional liquid formulations in enhancing plant growth, improving yields, protecting crops from pest and disease, enhancing soil fertility, as well as quality of agricultural products. Hence, there is an urgent need for further research, systematic documentation, and scientific verification of traditional liquid formulations to ensure its widespread adoption and effectiveness in promoting organic agriculture. An attempt has been made to review the information on the use of traditional liquid formulations, which are crucial for empowering rural communities and addressing the persistent challenges associated with conventional agricultural practices.